Synthesis of Recombinant Human Hemoglobin With NH2‐Terminal Acetylation in Escherichia coli. (20th July 2020) - Natarajan, Chandrasekhar; Signore, Anthony V.; Kumar, Vikas; Storz, Jay F.
Abstract: The development of new technologies for the efficient expression of recombinant hemoglobin (rHb) is of interest for experimental studies of protein biochemistry and the development of cell‐free blood substitutes in transfusion medicine. Expression of rHb in Escherichia coli host cells has numerous advantages, but one disadvantage of using prokaryotic systems to express eukaryotic proteins is that they are incapable of performing post‐translational modifications such as NH2 ‐terminal acetylation. One possible solution is to coexpress additional enzymes that can perform the necessary modifications in the host cells. Here, we report a new method for synthesizing human rHb with proper NH2 ‐terminal acetylation. Mass spectrometry experiments involving native and recombinant human Hb confirmed the efficacy of the new technique in producing correctly acetylated globin chains. Finally, functional experiments provided insights into the effects of NH2 ‐terminal acetylation on O2 binding properties. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Gene synthesis and cloning the cassette to the expression plasmid Basic Protocol 2 : Selection of E. coli expression strains for coexpression Basic Protocol 3 : Large‐scale recombinant hemoglobin expression and purification Support Protocol 1 : Measuring O2 equilibration curves Support Protocol 2 : Mass spectrometry to confirm NH2 ‐terminal acetylation